Functionality of a hinge joint in endoprostheses with titanium and chirulen components - Bondar, Vitaliy; Sheykin, Sergiy; Grushko, Oleksandr; Sergach, Dmytro (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
The article deals with a study of functional characteristics of the “nitrided pure titanium-chirulen” friction pair and determination of the contact pressure. Pure titanium was examined. In order to increase its tribotechnical characteristics, ion-plasma thermocyclic nitriding (IPTN) and thermodiffusion nitriding (TDN) were used. Tests of the “nitrided pure titanium-chirulen” friction pair were carried out on an end friction machine with fresh frozen human blood plasma of 0 (І), А (ІІ) and В (ІІІ) groups as working fluid. It was found out that by its rub resistance and antifriction properties the “nitrided pure titanium-chirulen” friction pair significantly surpassed the “CoCrMo-chirulen” pair. It was revealed that titanium samples, hardened by TDN technology, had better results than after IPTN. Tests in blood plasma, unlike those in Ringer’s solution, reproduced operation conditions of an artificial joint, implanted into the human body, more correctly. The wear rate of a component with chirulen within the contact pressure range of 3.54-6.5 MPa actually did not change, while at pressure over 6.5 MPa the wear assumed a catastrophic character. Therefore when an endoprosthesis is chosen it is necessary to consider the patient’s body weight.